Learning Anxiety Andlearning Styles as Predictors of English Achievement among Eighth-Grade Students - Septiana, Ayu Rizki; Harianto, Afrizal (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2025)
This study investigates the extent to which learning anxiety and learning styles predict English achievement among eighth-grade students at SMP Negeri 1 Gondang. Employing a quantitative non-experimental research design, the study involved 40 students selected through purposive sampling. Data were collected using a learning anxiety questionnaire, a learning styles questionnaire, and an English achievement test. The data were analyzed through descriptive statistics and inferential statistical techniques, including Pearson Product Moment correlation and linear regression analysis using SPSS 26. The findings reveal that learning anxiety and learning styles simultaneously have a significant effect on students’ English achievement. Partially, learning anxiety shows a significant negative influence on English achievement, indicating that higher levels of anxiety are associated with lower performance in English. In contrast, learning styles do not demonstrate a significant partial influence on English achievement. These results highlight learning anxiety as a crucial affective factor in foreign language learning, particularly in English classrooms. Although learning styles may shape students’ learning experiences, they are not a decisive factor in determining achievement outcomes when examined independently. The study suggests that English teachers should pay greater attention to students’ emotional conditions, especially anxiety, and create supportive learning environments to minimize anxiety and enhance achievement. Future research is recommended to explore additional psychological and instructional variables that may contribute to English achievement.